The Models of Physical Intuition Students use Phenomenological Elements in Solving Physics Problems - Nur Rahmah; Darsikin Darsikin; Amiruddin Kade; Muslimin Muslimin (Universitas Muhammadiyah Makassar, 2020)
This research applied qualitative research which used descriptive method in order to analyze the use of intuition physics of students in solving physics problems. This research was conducted at SMA Al Azhar Palu. The subjects of this research are nine students, they are divided by three categories which are the high, middle and low categories. The average value obtained from the respondents' test results was 43,46 and the standard deviation was 21,71. Respondents with a high category are respondents who are above the value of 65,17. The instruments of the research used are the respondent selection test, analyzing the use of intuition physics and interview guidance. Data were collected through thinking-aloud activities, which of respondents do a test then write the answers on a paper while expressing matters related to what was written and recorded that using a handycame. Interviews were conducted as supporting data in analyzing the results of thinking-aloud. Based on the analysis of data, it is obtained by the model of intuitions physics which contains the p-prims. It consists of cuing priority, reliability priority and the conclusion.The use of appropriate physics intuition is useful to help students apply their mathematical skills in solving physics problems. The proper physics intuition model is through all stages of the p-prims elements obtained through student learning experiences related to physics. It is necessary to develop learning that considers the importance of using physics intuition as a performance framework for evaluating the progress of students' problem solving processes better and more productively.